Gender Inequality in Endogamous Marriage Practices: : A Study of the Arab Community in Palembang - Sukmawati, Lilis; Tuhuteru, Ajuan (Al-MUNZIR, 2025)
The world is now entering the 5.0 era where humans are required to think forward and be innovative in facing the challenges of the times. Gender equality is an important issue, but the gender gap is still evident, especially in terms of women's rights. Although many Indonesian women have occupied public positions, patriarchal perspectives are still widely found, one of which is in the practice of endogamous marriage. The purpose of this article is to analyze the gender perspective of Palembang Arabs who practice endogamous marriage. The approach used in this article is descriptive qualitative. The informants interviewed totaled five people, two women and three men. The data collection techniques used are observation, interview and documentation. The results showed that men consider women (sharifah) of Arab ethnicity to be submissive so that things that are prohibited such as not being highly educated, not being allowed to have other activities outside the home, and limiting their duties to only taking care of the house and children are things that make them appropriate or not to be used as wives. on the other hand, for women, education is something that is allowed in religion as the hadith which means "pursue knowledge from the mother's cradle to the grave", kitchen affairs are not only women's affairs but also men's affairs, so there is a need for communicationKeywords: Gender issues; Endogamous marriage; Gender inequality, Palembang Arab Village